Incidence and Risk Factors of Toxoplasmosis in a Cohort of Human Immunodeficiency Virus‐Infected Patients: 1988‐1995 - François Belanger; Francis Derouin; L. Grangeot‐Keros; Laurence Meyer (1999)
The incidence of cerebral and extracerebral toxoplasmosis among 1,699 HIV-infected patients followed in the SEROCO and HEMOCO cohorts (1988–1995) was studied. It increased from 0.7 per 100 person-years in 1988 to 2.1 per 100 person-years in 1992, as a result of the increasing prevalence of patients with CD4 cell counts below 200/µL. It decreased thereafter to 0.2 per 100 person-years in 1995, while the proportion of patients receiving specific prophylaxis was increasing. A Toxoplasma antibody titer of >150 IU/mL was an important predictor of toxoplasmosis (adjusted relative risk [aRR], 3.6 [95% confidence interval, 2.1–6.0]), independent of a CD4+ cell count of <200/µL (aRR, 20.8) and specific prophylaxis (aRR, 0.2 [0.1–0.3]). The median CD4+ cell count was 389/µL at the time the antibody titer was first noted to be >150 IU/mL, while the median CD4 cell count at onset of toxoplasmosis was 58/mL. Thus, disease was diagnosed 10 days to 74 months after the rise in Toxoplasma antibody titers. While the risk factors for development of toxoplasmosis remain incompletely defined, the importance of specific prophylaxis for patients with low CD4 cell counts and high Toxoplasma antibody titers is supported by these findings